Debt Maturity and Financial Report Quality: A Dual Approach to Enhancing Investment Efficiency - Vista Yulianti; Sindik Widati; Ahmad Bukhori Muslim (Jurnal Akuntansi Bisnis Pelita Bangsa, 2025)
This study examines the impact of Financial Report Quality (FRQ) on Investment Efficiency (IE), with Debt Maturity (DM) as a moderating variable. High-quality financial reporting is expected to reduce information asymmetry and support optimal investment decisions, while the structure of debt maturity may strengthen or weaken this relationship. The research uses secondary data from the financial statements of companies listed on the Indonesia Stock Exchange (IDX) over the period 2020–2024. The sample is selected using purposive sampling, resulting in a final set of firms that meet the criteria for analysis. Variables are measured using established proxies, and the data is analyzed with Partial Least Squares (PLS) to test measurement validity, reliability, and structural relationships. Results indicate that FRQ significantly enhances IE, and DM plays a moderating role in strengthening this relationship. The findings provide practical implications for corporate managers in structuring financial reporting and debt maturity to achieve better investment efficiency. This research also contributes to the literature by integrating FRQ and DM within the investment efficiency framework.